Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

E-Learning in Bangladesh: A Study of Teachers’ Behavioral Orientation and Affective Alignment in the Post-New Normal - Shamim Miah, A.S.M; Rasel Kabir, Md; Sultana, Sarmin (Contemporary Research in Education and English Language Teaching, 2020)
This study explores the teachers’ behavioral and affective orientation to e-learning that is in practice at all the levels of education in Bangladesh i.e. primary school, secondary school, higher secondary school, college, and university. By investigating the reasons for such disarray, it proposes solutions to overcome them. It acquired its data through online surveys followed by quantitative analysis through descriptive inferential analogies of the logarithmically represented findings. The result of the study documents that teachers’ preparation, technological know-how and adaptation to the e-learning platforms, their methods of teaching, measurement of outcomes, and mapping of curricula suggest that e-learning in Bangladesh is vitiated due to the diffusion in the teaching staff demographics and diluted apprehension of the e-learning. The paper’s primary findings show that Bangladesh’s progress from Education 1.0 to Education 3.0 is more affective and behavioral than cognitive in the implementation; wherein, the very concept of e-learning is diluted or spun around the idea of education via some usage of technology only, more specifically web conference applications which is indicative of Education 2.0 practices. There is no distinction made that separates online learning from e-learning, e-learning from distance and distance from blended learning, etc. in the current environment.

Integrating ICT in English Language Teaching in Bangladesh: Teachers’ Perceptions and Challenges - Khan, Nafis Mahmud; Kuddus, Khushboo; Kuddus, Khushboo; School of Humanities (English), KIIT Deemed to be University, Bhubaneswar, Odisha, India. (Rupkatha Journal on Interdisciplinary Studies in Humanities, 2020)
The integration of Information and Communication Technology (ICT) in Education especially, in English Language Teaching (ELT) in secondary schools of Bangladesh has been existing for a decade now. However, the status of actual implementation is quite different from the adoption and initiatives taken to integrate ICT in ELT. Therefore, the study aims to investigate the secondary level English language teachers’ attitude towards integration of ICT in Communicative Language Teaching (CLT) and the factors inhibiting the use of it. Further, the paper attempts to examine the challenges faced by the secondary level English teachers of Bangladesh in using ICT in language teaching effectively. In an attempt to examine the attitude of teachers in using ICT in ELT, a quantitative research is designed with a close ended questionnaire to collect the data from a sample of 100 secondary English language teachers of various schools of Bangladesh. The data of the responses is quantified and is analyzed by SPSS 20 program. The obtained data from the questionnaire is examined in order to investigate the perceptions of the secondary level English language teachers towards ICT integrated language teaching and the challenges of the implementation of ICT in ELT. In conclusion, the outcome of the research would provide significant information about the attitude of the teachers towards ICT integration in ELT and the challenges faced by them and hence, the study would help the policy makers and the teachers to enhance the effectiveness of using ICT in ELT.

Compendium of Social Protection Research in Bangladesh - Government of Bangladesh (The General Economics Division (GED), Bangladesh Planning Commission, 2020)

Secondary Education During Lockdown Situation Due to Covid-19 Pandemic in Bangladesh: Teachers’ Response on Online Classes - Farhana, Z; Tanni, S; Shabnam, S; Chowdhury, S (Journal of Education and Practice, 2020)
Online classes started in many secondary schools one month after the compulsory closure of all education institutions in Bangladesh. This study explores the current scenario as well as challenges of adaptation of online classes in secondary education in terms of teachers’ experience. The study followed sequential exploratory mixed-method approach. Five secondary teachers were interviewed and 54 secondary teachers from 17 districts in Bangladesh were surveyed over telephone, Google forms and by email. The quantitative data was analyzed with Microsoft Excel and the thematic analysis approach had been followed for the qualitative one. The findings revealed that a good number of teachers have started teaching online by using social media platforms despite of not having any training or experience. Very few respondent teachers were found to take online examination; instead they are trying to assess the students from the feedback of given home works and home assignments. Teachers are facing numerous challenges like deficit of digital equipment, lack of expertise, unfamiliarity with the LMS, proficiency in assessment technique etc. The paper concludes with few recommendations such as providing proper devices to the teachers and students to participate in online class; facilitate rigorous training to enhance technology-based skills and capacities of the teachers so as to get the expected outcome.

TV-Based Learning in Bangladesh: Is it Reaching Students? - Biswas, Kumar; Asaduzzaman, T.M.; Evans, David; Fehrler, Sebastian; Ramachandran, Deepika; Sabarwal, Shwetlana (World Bank, 2020)
Is TV-based learning during COVID-19 school closures in Bangladesh reaching students? Most students (86 percent) within our sample of more than 2,000 Grade 9 stipend recipients are aware of government provided TV-based learning programs; yet only half of the students with access to these programs choose to access them. Also, very few students (21 percent) have access to government provided online learning programs, and among those that do, only about 2 percent choose to access them. There is a perceptible decline in the time students spend studying at home after school closures. This may be linked to the fact that 1 in 2 parents claim they are unable to help their children with new topics. Despite lower education, mothers are significantly more likely to be involved in the child’s education compared to fathers. Most students (90 percent) claim they have a supportive environment at home for studying. This is true for both boys and girls. Finally, nearly 65 percent of households in our sample report declines in income and 28 percent had to decrease the amount of food consumed within the household in the previous week.
Keywords: Access to Education; Distance Learning; Education; Online Learning; School Closure; Secondary Education; ___working_potential_duplicate

Making Vision 2041 a Reality: Perspective Plan of Bangladesh 2021-2041 - General Economics Division, Bangladesh Planning Commission, Ministry of Planning, Government of the People’s Republic of Bangladesh (2020)

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Five lessons learnt from Bangladesh's experience responding to COVID-19 - Sarwar, Mohammad Afzal Hossain; Hossain, Iqbal; Kaye, Tom (EdTech Hub, 2020)
by Md. Afzal Hossain Sarwar (a2i), Iqbal Hossain (UNICEF Bangladesh) and Tom Kaye (EdTech Hub) In recent months, the EdTech Hub has produced a range of documents to support and guide countries as they develop and implement plans to help students keep learning during school closures. Some of the work we have produced includes: a guide to a five-part response…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Challenges and Developments in the Higher Education System of Bangladesh: Keys to Way Forward - Chowdhury, Mahfuzul Hoque; Absar, Mir Mohammed Nurul; Quader, Syed Manzur (Handbook of Education Systems in South Asia, 2020)

COVID-19 and Bangladesh: challenges and how to address them - Anwar, Saeed; Nasrullah, Mohammad; Hosen, Mohammad Jakir (Frontiers in Public Health, 2020)
As the coronavirus outbreak quickly surges worldwide, many countries are adopting non-therapeutic preventive measures, which include travel bans, remote office activities, country lockdown, and most importantly, social distancing. However, these measures face challenges in Bangladesh, a lower-middle-income economy with one of the world's densest populations. Social distancing is difficult in many areas of the country, and with the minimal resources the country has, it would be extremely challenging to implement the mitigation measures. Mobile sanitization facilities and temporary quarantine sites and healthcare facilities could help mitigate the impact of the pandemic at a local level. A prompt, supportive, and empathic collaboration between the Government, citizens, and health experts, along with international assistance, can enable the country to minimize the impact of the pandemic.

Students perception of mobile learning during COVID-19 in Bangladesh: university student perspective - Biswas, Bikram; Roy, Sajib Kumar; Roy, Falguni (Aquademia, 2020)
The aim of this study is to measures the student’s perception of using mobile for learning during COVID-19 in Bangladesh especially at the university student’s perspective. During the COVID-19 pandemic period, mobile learning may help the students to fulfill the study gap. Due to COVID-19 pandemic 213 countries, higher education has affected all over the world of June 2020. Although all of the developed countries considered mobile learning as an effective tool for education, it is not used properly in Bangladesh. This survey method conducted on 416 students from different university students in Bangladesh to understand the student’s perception of using mobile phones as a learning system. The findings of this study show that most of the students at the university level have a positive perception of m-learning. This study revealed that m-learning is very helpful to recover the study gap during this COVID-19 pandemic time and the findings of this study will help the education policymaker as well as the educational institutions to incorporate mobile learning technology for the whole system where social media may enhance the process of teaching and learning.

An interactive math braille learning application to assist blind students in Bangladesh - Nahar, L; Sulaiman, R; Jafaar, A (Assistive Technology, 2020)
Due to the lack of affordable assistive tools for learning mathematics, blind students in Bangladesh still use outdated learning tools like Tailor Frame. Therefore, demand for a low-cost technological tool is there that will help the blind students to learn math braille and calculate numbers more easily. To provide an effective and affordable assistive tool, this study begins with a needs assessment study to identify the basic needs of blind students in learning math braille and solving mathematical calculations. Afterward, a mobile phone based interactive assistive application is proposed to improve the learning facilities of math braille using Nemeth code for blind students in Bangladesh. Interfaces of the application are designed based on their needs. Besides, interaction methods (such as, hearing & touching) of blind students with the physical world were another criterion in designing very interactive interfaces that provide self-learning facilities. The interfaces are evaluated by the teachers, experts, and end users in order to identify the usability. The evaluation shows a promising result toward the acceptability of the designed application. Therefore, this application can be helpful for the blind students to learn math braille using Nemeth Code.

Adolescence in the Time of Covid-19: Evidence from Bangladesh - Baird, Sarah; Seager, Jennifer; Sabarwal, Shwetlena; Guglielmi, Silvia; Sultan, Maheen (2020)
This note examines the effects of COVID-19 and subsequent economic and educational disruptions on adolescent well-being in Bangladesh. The analysis is based on data from 2,095 in-school adolescents aged 10–18 collected preCOVID-19 (February–March 2020) through a field survey for an ongoing impact evaluation, and a follow-up virtual survey undertaken early in the pandemic (May–June 2020). Findings show large household-level economic impacts associated with increased food insecurity, anxiety, and mental health issues among adolescents. In addition, school closures have decreased adolescents’ access to learning, increased time spent on household chores, and affected future job aspirations. The impacts are particularly large for girls and for adolescents from more vulnerable households. Policy makers need to consider policies that facilitate school return, targeting girls and the most vulnerable. They also need creative school-based programming to address the likely long-run physical and mental health effects of COVID-19 on young people.

COVID-19 Response and Recovery Plan - Government of Bangladesh (2020)

Making Vision 2041 a Reality: Perspective plan of Bangladesh 2021-2041 - Ministry of Planning (Ministry of Planning,Government of the People’s Republic of Bangladesh, 2020)

Impact of COVID-19 on the institutional education system and its associated students in Bangladesh - Emon, Efta Khairul Haque; Alif, Ashrafur Rahman; Islam, M. Shahanul (Asian Journal of Education and Social Studies, 2020)
Keywords: Bangladesh; COVID-19; Coronavirus; education; impact; poverty.

Bangladesh Education Sector Analysis - GPE (2020)

Bangladesh - COVID 19 School Sector Response Project (English) - World Bank (2020)

COVID-19 boosts digitization of higher education in Bangladesh - Rahman, M; ul-Aziz, M; Ahmed, S (2020)

Coronavirus Outbreak, Schooling and Learning: Study on Secondary School Students in Bangladesh - Asadullah, N; Bhattacharjee, A; Tasnim, M; Mumtahena, F (2020)

Education sector plan (ESP) for Bangladesh: Fiscal years 2020/21-2024/25 - MoE (Ministry of Education, 2020)

Mental health and learning: BRAC’s response in Bangladesh during Covid-19 - Ahmad, J; Mariam, E; Sadaf, B; Sarwar, S; Siddique, S; Zaman, S (2020)

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - GPE (Global Partnership for Education, 2020)

WFP and Government of Bangladesh deliver high-energy biscuits to school children affected by COVID-19 school closures - WFP (ReliefWeb, 2020)
English News and Press Release on Bangladesh about Education, Food and Nutrition and Epidemic; published on 19 May 2020 by WFP

Human Development Report 2020: The Next Frontier - Human Development and the Anthropocene. Bangladesh. - United Nations Development Programme (Human Development Report, 2020)
Keywords: ___working_potential_duplicate

Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - Das, H (a2i, 2020)

How BRAC is supporting Bangladesh to continue education in a pandemic - Chowdhury, Zaian; Islam, Rubab; Saltmarsh, Sarah-Jane (2020)
Keywords: ___working_potential_duplicate

Staying Tuned Radio Programming for Sustained Behaviour Change and Accountability in Cox’s Bazar, Bangladesh - Ergül, H (UNICEF, 2020)

Final Report on: Assessment of Distance Learning Initiative of the Government of Bangladesh during COVID-19 Pandemic - a2i (2020)

A Rapid Assessment: Impact of COVID-19 on Education in Bangladesh - BRAC (Advocacy for Social Change (ASC), BRAC, 2020)

Summative Evaluation of GPE's Country-level Support to Education. Bangladesh - Results for Development (Universalia, 2020)

A rapid assessment: Impact of COVID-19 on Education in Bangladesh - Advocacy for Social Change, BRAC; BRAC Education Programme (2020)

Audio Lessons Through Radio for Primary Education Set for Launch -With Support from UNESCO CapED Programme for COVID-19 Educational Response for Bangladesh - UNESCO (UNESCO, 2020)

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (2020)
Keywords: ___working_potential_duplicate

ঘরে বসেই শিক্ষা - EduHub Bangladesh (LearnFromHome, 2020)
ঘরে বসেই শিক্ষা

Parenting and child’s (five years to eighteen years) digital game addiction: A qualitative study in North-Western part of Bangladesh - Keya, Farah Deba; Rahman, Md Mostafizur; Nur, M. Tareq; Pasa, Md Kamal (Computers in Human Behavior Reports, 2020)
Globally, addiction to digital game among the children and adolescents is a growing concern due to its increasing rate of users and adverse effects on their personal including health and social life. Reviewing the literatures shows a number of factors for child’s digital game addiction. Of the literatures, only a few plausibly shows some form of parenting be a cause for digital game addiction, but under what conditions of parenting influence child to be addicted to digital game is not adequately addressed. Aiming to address the gap, a qualitative study was conducted in North-western Bangladesh using Ethnographic Interview with children and Indepth Interview with parents. The data was analyzed manually following thematic framework. The result of the study shows troubled child-parent relationship and parental attitudes for making their child competitive in education, parental neglect, loneliness and anxiety of the child, and permissive parenting are attributed to digital game addiction. Its social basis is emanated from the family’s asymmetrical role in a market based society. Making a child competitive and capable for future market system is over prioritized, whereas providing emotional security is undermined. It also argued that in a capitalistic society, parents has turned tobe a less authoritative figure to deal children’s issue due to the father’s inability to address economic needs of the family adequately and mothers’ economic dependence to their male counter-part. In such a context, parents are compelled to minimize the gap by offering or allowing child to digital game and so gradually children become addicted to digital game. This argument supported the idea of Frankfurt school on how people attracted and depended on culture industry.
Keywords: Digital game addiction; Economic pressure; Emotional security; Parental neglect; Permissive parenting; Troubled child-parent relationship

Characteristics of effective teacher education in low- and middle-income countries: an overview (HDR10A) - Haßler, Björn; McBurnie, Chris; Allier-Gagneur, Zoe; Damani, Kalifa (EdTech Hub, 2020)
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

COVID-19 Response and Recovery Plan - Ministry of Primary and Mass Education (Government of People's Republic of Bangladesh, 2020)

How to re-imagine learning in the wake of Covid-19 (EdTech Hub, 2020)
Last week the EdTech Hub, #NextGenEdu, and Education Development Trust convened experts, policymakers, and implementers to discuss their visions for a reimagined approach to learning in the wake of coronavirus.  The invited speakers were: Mohibul Hasan Chowdhury, Deputy Minister of Education, Bangladesh Ministry of Education Jim Ackers, Regional Education Advisor, UNICEF South Asia Regional Office Sonam Wangchuk, Founder, Students’ Educational…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

New Brief: Monitoring Distance Learning During the Covid-19 Pandemic - Bashir, Amreen; Groeneveld, Caspar; Kaye, Tom (EdTech Hub, 2020)
In the initial rush to respond to school closures, countries focused on rolling out distance education. Policy-makers now realise that effective distance education requires robust data generated via high-quality monitoring. This blog highlights the findings of a brief synthesising effective practices in monitoring distance education.  Since March 2020, the Covid-19 pandemic has impacted 36 million learners in Bangladesh. Schools closed…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Annual Primary School Census 2019 (Draft) - MoPME; Directorate of Primary Education (2020)

Dearth of research in Bangladeshi universities - Momin, S (2020)

Recovery of Learning Loss Created Due to COVID-19 Crisis: Analysis of Bangla Learning Outcomes and Identification of Content - NAPE; Room to Read (2020)

2019 Civil Society Organization Sustainability Index - for Asia 6th Edition – December 2020 - USAID (United States Agency for International Development Bureau for Democracy, Conflict and Humanitarian Assistance Center of Excellence on Democracy, Human Rights and Governance, 2020)

UNICEF scales up support to keep children learning, as COVID-19 forces schools to close - UNICEF (2020)

Covid-19 disrupts education in rural Bangladesh - Uttom, Stephan; Rozario, Rock (UCA News, 2020)
Pupils and teachers lament lack of access to online classes due to poverty

TV-Based Learning in Bangladesh: Is it Reaching Students? - World Bank (World Bank Group, 2020)
Keywords: ___working_potential_duplicate

The state of education in urban slums of Bangladesh - Khondoker, Zarine Anan (BRAC Institute of Governance and Development, 2020)

Education sector plan (ESP) for Bangladesh Fiscal years 2020/21-2024/25 - Ministry of Education (Ministry of Education, 2020)

Education Sector Plan (ESP) for Bangladesh Fiscal Years 2020/21-2024/25 - MoE (2020)

Summative Evaluation of GPE’s Country-Level Support to Education: Bangladesh - Universalia (2020)

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Understanding the first and second digital divides in rural Bangladesh: internet access, online skills, and usage - Siddiquee, Muhammad Shahadat Hossain; Islam, Md. Saiful (Digitization Series, 2020)

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Human Development Reports - United Nations Development Programme (2020)

How many children and young people have internet access at home - UNICEF; ITU (2020)

Global Education Monitoring Report 2020: Inclusion and Education – All Means All - UNESCO (UNESCO, 2020)

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)

Guidance on Distance Learning Modalities to Reach All Children and Youth During School Closures - UNICEF Regional Office for South Asia (2020)

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Evaluation of the Global Education Cluster (GEC) Action (2017-2019): Strengthening Coordination of Education in Emergencies - UNICEF (2020)
This evaluation was conducted between November 2019 and February 2020, with the main purpose of generating learning, for Global Education Cluster (GEC) managers and other stakeholders, on ‘what worked where and how’ in the DG/ECHO grant to the GEC (2017-2019). The evaluation also serves an accountability function by providing an independent assessment of the GEC Action against its intended results. Building on 2 in-depth country case studies in Bangladesh and North East (NE) region of Nigeria, and a broader multi-country case study, through a desk review of relevant documents, key informant interviews and an online survey administered with education cluster/coordination team actors, the report generates findings related to the relevance, effectiveness, efficiency, coordination and connectedness of the grant. The evaluation also produced 5 recommendations, validated through a learning workshop held in Brussels, which informed the process of development of the new GEC strategy (2020-2021).

Assessing the real-life socio-economic scenario of established slums in Dhaka: the cases of Korail and Sattola - Bashar, Raisa; Tonmoy, Sirajus; Ria, Alvira; Khan, Nazmul (European Online Journal of Natural and Social Sciences, 2020)
The research aims to assess the current situation of three primary socioeconomic indicators, namely education, health and water availability at the two most established slums of Bangladesh's capital Dhaka-Korail and Sattola. Surveys, using cluster and then random sampling to target households, and analysis, found that both slums' children's education level was moderate with 52%-68% and 20%-28% availing primary and secondary education, respectively; several NGOs had helped to establish brick-and-mortar latrines and disseminate necessary and effective awareness about sanitation; and surveyed slum dwellers were economically strong, with 68%-70% of the interviewed households' income levels being 10,000-15,000 BDT (USD 118-178) per month. A comparative analysis with national level statistics also yielded that the conditions in these slums are truly better than previously thought. Primary recommendation includes in-depth monitoring to understand why such large numbers live in slums, even though they can afford better.
Keywords: ⚠️ Invalid DOI

Educational Technology in Developing Countries: A Systematic Review - Rodriguez-Segura, Daniel (EdPolicyWorks Working Paper, 2020)
Keywords: ___working_potential_duplicate

Adolescent problematic internet use and parental mediation: A Bangladeshi structured interview study - Chandrima, Rubaiya Matin; Kircaburun, Kagan; Kabir, Humyon; Riaz, Baizid Khoorshid; Kuss, Daria J.; Griffiths, Mark D.; Mamun, Mohammed A. (Addictive Behaviors Reports, 2020)
Internet-related problems such as excessive internet use, problematic internet use (PIU), and internet addiction, are becoming increasingly studied among Bangladeshi adult students, but there has been little research among adolescents. In Bangladesh, there has been no research examining the role of parental mediation in their children's internet use. Therefore, the present structured interview study investigated Bangladeshi adolescent PIU and its associated socio-demographics, internet use behaviors, and the parental mediation role among 350 high school students residing in Dhaka. The results showed that 84 of adolescents (24.0%) were classified as having PIU (cut-off score of ≥ 50 on the Internet Addiction Test) and nine adolescents (2.6%) were classified as having a severe dependency on the internet (cut-off score of >80 on the Internet Addiction Test). According to hierarchical regression analysis, significant PIU correlates included lower academic results, both parents' lower education, mother working outside the home, more than four days' weekly internet use, more than two hours daily internet use, and active mediation. Additionally, internet use behaviors (i.e., internet use locations, devices, purposes, and applications) and parental internet mediation dimensions other than active mediation (i.e., restrictive mediation, active mediation internet safety, monitoring, and technical mediation) were significantly related to PIU in t-tests and correlation analysis respectively. However, they were non-significant in the hierarchical regression analysis when included into equation altogether. The present study's findings will be helpful in developing country-level policymaking decisions and facilitating future research in the country.
Keywords: Bangladeshi adolescence; Internet addiction; Internet use behaviors; Parental mediation; Problematic internet use

Education and Covid-19 response: bringing schools and learning back on track - Ahmed, Manzoor; Rahaman, Mostafizur; Hossain, Syed Shahadat; Ahmed, Ghiasuddin (Education Watch/Campaign for Popular Education (CAMPE), 2020)

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

COVID-19 response and recovery plan: education sector - Ministry of Primary and Mass Education (Ministry of Education, Government of the People’s Republic of Bangladesh, 2020)

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)